2002
DOI: 10.1021/ja011832f
|View full text |Cite
|
Sign up to set email alerts
|

Artifacts in the Electron Paramagnetic Resonance Spectra of C60 Fullerene Ions:  Inevitable C120O Impurity

Abstract: Aspects of the electron paramagnetic resonance (EPR) spectra of C60 n-fulleride ions (n ) 2, 3) and the EPR signal observed in solid C60 are reinterpreted. Insufficient levels of reduction and the unrecognized presence of C120O, a ubiquitous and unavoidable impurity in air-exposed C60, have compromised most previously reported spectra of fullerides. Central narrow line width signals ("spikes") are ascribed to C 120O n-(n ) odd). Signals arising from axial triplets (g ∼ 2.0015, D ) 26-29 G) in the spectrum of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 37 publications
8
74
1
Order By: Relevance
“…Such ESR spectra resemble closely those reported at high temperatures for many fullerides, comprising a very narrow 'spike' ESR line with DH pp of 1-2 G, frequently superimposed on a much broader signal of C À 60 ions [1]. Recent experiments have shown that the frequently debated origin of this sharp ESR signal is related to the presence of C 120 O of an unrecognized impurity in the air-exposed samples of C 60 [13,14]. Specifically, this narrow ESR signal has been assigned to a doublet spin state (S = 1/2) of C 120 O À which also accounts for the frequent temporal reduction of the C À 60 ESR line intensity, as C 60 is more easily Fig.…”
Section: Methodssupporting
confidence: 77%
“…Such ESR spectra resemble closely those reported at high temperatures for many fullerides, comprising a very narrow 'spike' ESR line with DH pp of 1-2 G, frequently superimposed on a much broader signal of C À 60 ions [1]. Recent experiments have shown that the frequently debated origin of this sharp ESR signal is related to the presence of C 120 O of an unrecognized impurity in the air-exposed samples of C 60 [13,14]. Specifically, this narrow ESR signal has been assigned to a doublet spin state (S = 1/2) of C 120 O À which also accounts for the frequent temporal reduction of the C À 60 ESR line intensity, as C 60 is more easily Fig.…”
Section: Methodssupporting
confidence: 77%
“…However, there was a controversy 27 on whether the low-spin/high-spin gap is very small (below one wavenumber 28 ) or rather of the order of 600 wavenumbers 29 . Recently, this problem was carefully reconsidered and it was shown that activated behaviors of C N − 60 which were observed so far and used to determine the gap are in fact due to C 120 O impurities 30,31 . However, the work clearly reconfirms that iso-lated C N − 60 ions (N = 2, 3) are in the low-spin state.…”
Section: Results For C60mentioning
confidence: 99%
“…With these selection rules and the spectrum of the top given in (46), we find that the ground state and lowest excitations have quantum numbers (LK) = (10), (2 −2), (4 −4), (32), (30). The next higher state in energy is (6−6) which, according to (50), is allowed to mix with (6 −2).…”
Section: − 60mentioning
confidence: 94%
“…1070 Recently, we prepared a single crystal of PhCN) 2 , which forms a 3D framework built of alternating Cp à Co þ and C 60 2À ions with channels accommodating solvent molecules (Fig. 154).…”
mentioning
confidence: 99%